Implementing a Collaborative Sepsis Protocol on the Time to Antibiotics in an Emergency Department of a Saudi Hospital: Quasi Randomized Study - Rifat S. Rehmani; Javed I. Memon; Ayman Al-Gammal (Critical Care Research and Practice)
Background. The objective of this study is to evaluate the impact of an ED sepsis protocol on the time to antibiotics for emergency department (ED) patients with severe sepsis. Methods. Quasiexperimental prospective study was conducted at the emergency department. Consecutive patients with severe sepsis were included before and after the implementation of a sepsis protocol. The outcome measures were time from recognition of severe sepsis/septic shock to first antibiotic dose delivery and the appropriateness of initial choice of antibiotics based on the presumed source of infection. Results. There were 47 patients in preintervention group and 112 patients in postintervention group. Before implementation, mean time from severe sepsis recognition to delivery of antibiotics was 140 ± 97 minutes. During the intervention period, the mean time was 68 ± 67 minutes, with an overall reduction of 72 minutes. The protocol resulted in an overall improvement of 37% in the compliance, as 62% received appropriate initial antibiotics for the presumed source of infection as compared to 25% before the start of protocol. Conclusion. Implementation of ED sepsis protocol improved the time from recognition of severe sepsis/septic shock to first antibiotic dose delivery as well as the appropriateness of initial antibiotic therapy.